A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific - Betancur-R., Ricardo; P., Arturo Acero (Zootaxa, 2006)
Notarius armbrusteri n. sp. is described from specimens purchased in the fish market of Buenaventura, Valle del Cauca, Colombia. The species is distinguished from other eastern Pacific species of Notarius by the following combination of features: mouth small, width 11.1–11.8% SL; eye large, diameter 4.3–4.9% SL; distance between anterior nostrils 6.1–6.9% SL, distance between posterior nostrils 5.9–6.9% SL; short maxillary barbels, length 20.5–22.2% SL; and gill rakers on first arch 3–4+8–9 (total 11–13). Based on mitochondrial evidence (cytochrome b and ATP synthase 8/6, total 1937 base pairs), the new species is closely related to N. insculptus, from the Pacific Panama. An updated key to identify the eight described species of Notarius from the eastern Pacific is provided.